2023
DOI: 10.1212/cpj.0000000000200162
|View full text |Cite
|
Sign up to set email alerts
|

Conversion Rate of Essential Tremor to Essential Tremor Parkinson Disease

Abstract: Background and ObjectivesThere has been a long-standing dialog as to whether essential tremor (ET) increases the risk of developing Parkinson disease (PD). While there are relevant cross-sectional data, there are almost no longitudinal prospective data. We quantified the conversion rate from ET to ETPD in a prospective longitudinal cohort study of patients with ET. We compared the observed rate with that reported in the epidemiologic literature.MethodsWe enrolled patients with ET in a prospective, longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…This suggests that there is a subset of patients with criteria for ET, thus presenting postural bilateral hand tremor, that are prone to develop PD in the long run. This is in accordance with longitudinal studies showing an increased incidence of PD in ET populations [ 23 ], and to neuropathological studies showing and excess of lewy-body pathology in ET patients [ 24 ] (although cerebellar Purkinje cell alterations, found in other cerebellar neurodegenerative disorders, seem to be the main neuropathological finding in ET [ 25 ]).…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that there is a subset of patients with criteria for ET, thus presenting postural bilateral hand tremor, that are prone to develop PD in the long run. This is in accordance with longitudinal studies showing an increased incidence of PD in ET populations [ 23 ], and to neuropathological studies showing and excess of lewy-body pathology in ET patients [ 24 ] (although cerebellar Purkinje cell alterations, found in other cerebellar neurodegenerative disorders, seem to be the main neuropathological finding in ET [ 25 ]).…”
Section: Discussionsupporting
confidence: 90%
“…A recent postmortem study indicated that 1 in 4 ET cases have Lewy pathology (LP); in two-thirds, LP was observed in the LC [13,14]. In Parkinson's disease (PD), a related disorder [15,16], sleep disruption observed during the prodromal period may involve the deposition of LP in brainstem structures such as the LC.…”
Section: Introductionmentioning
confidence: 99%